MUSICAL AND AESTHETIC EDUCATION OF THE PERSONALITY - Nishanbekova Jadira Urinbaevna (Bright Mind Publishing, 2025)
The article deals with musical and aesthetic education of the individual, the main types of educational activities in a music lesson in a comprehensive school.
Keywords: Music, aesthetic education, personality, types of educational activities, musical culture.